Immunotherapy and radiation for head and neck cancers - Schoenfeld, Jonathan (Henry Stewart Talks, 2023)
Head and neck cancer, PD-1 blockade, Predictive markers, PDL1 expression and HPV status, Keynote 48, Neoadjuvant immunotherapy, Immunotherapy trials, Keynote 689, IAP inhibitors